Penegakan Hukum terhadap Pelaku Tindak Pidana Penambangan Pasir Secara Illegal - Anastasia Esa Ananta (Program Studi Ilmu Hukum, Universitas Kuningan, 2024)
Mining is a natural resource that cannot be renewed so it must be managed as well as possible, efficiently and transparently and paying attention to the environmental impacts resulting from mining activities. The rampant illegal sand mining that occurs in Batam, Indonesia can certainly cause environmental damage. The aim of this research is to determine and analyze the regulation and law enforcement against perpetrators of illegal sand mining crimes. The research method used in this research is descriptive-analytic with a juridical-normative type of research. The results of research on regulations regarding perpetrators of illegal sand mining crimes are regulated in Article 158 which reads